SINGLE-USE PLASTIC: REDUCE OR IGNORE - Noor Aziah Abdullah; Cheang Hui; Mohd Harryzman Harun (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Malaysia is one of the worst countries overflowed with tonnes of single-use plastic waste in Asia. Our reliance on these plastics means we are accumulating waste at a staggering rate. The users flavor single-use plastic due to the fact durable, cheap, easy to obtain, and makes packaging convenient. Single-use plastic packaging such as plastic cups and straws, wrapper, plastic cutlery, and plastic bags are used by humans every day. The overuse of single-use plastic harmed the ecosystem, human health, and the image of Malaysia. Therefore, this study aims to create public awareness about the seriousness of single-use plastic waste’s effect on their living environment and encourage the audiences to reduce using the these-use plastic product. An in-depth interview has conducted with two environmental-based experts and an environmental organization to understand more information about the single-use plastic issue in Malaysia. A few alternative materials to replace single-use plastic has been introduced: edible cutlery, bio-degradable grocery bags, paper bag, bamboo, and paper straw. Hence, the public must be concerned about single-use plastic issues to reduce the unnecessary usage of plastic, which will increase the burden on the environment. This study will benefit the Government and agencies related to how to solve the single-use plastic issue.